Orca echoes resource guide - Van Tol, Alex (Orca Book Publishers, 2010)
The Orca Echoes Resource Guide helps teachers open the door for meaningful classroom discussion. Professionally written guides with curriculum connections, writing exercises, discussion questions and activities are provided for each title in the Orca Echo.